Educação Matemática e Sociedade - De Mattos, Adriana Cesar [UNESP] (My University, 2011)
The paper's aim is to justify the creation of the line of research Mathematics Education and Society in the Graduate Program of Mathematics Education (PPGEM), UNESP (Rio Claro, SP). In a brief history of the constitution of the mathematics education community, the categories culture and society were emphasized. A brief summary of sociology is presented, drawing on classical sociologists and contemporary authors. The group EMsociedade is presented, and its purpose, which is to be part of the PPGEM to establish a space for discussions between students and supervisors from the Graduate Program, elementary and middle school teachers, and others who have interest in the subject. One of the arguments defended by the group is presented: institutionalized mathematical knowledge in the Twentieth Century is a commodity. Finally, some future considerations are outlined, including the expectation that the line of research Mathematics Education and Society will be included in the PPGEM.
Mathematics education and society
Keywords: Commodity; Mathematics education; Society; Sociology